2016
DOI: 10.1002/hyp.10987
|View full text |Cite
|
Sign up to set email alerts
|

Modelling evaporation processes in soils from the Huasco salt flat basin, Chile

Abstract: 40The results presented in this study are important as they allow quantifying the evaporation that occurs in 41 bare soils from Altiplano basins, which is typically the main water discharge in these closed basins. 42

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Instantaneous evaporation in the basin is proportional to the potential evaporation, and it can be as large as 90% of the precipitated water [ Vega , ], whereas the total evaporated water from the Salar can also be written as proportional to the potential evaporation [ Hornberger et al , ]. The proportional constant for computing total evaporation from the Salar is given, among others, by the size of the shallow wetland and its salinity [ de la Fuente and Niño , ], the ground water depth, and the soil salinity and humidity [ Nachshon et al ., ; Aminzadeh et al ., ; Hernández‐López et al ., ]. In this manner, the reduction in the potential evaporation may imply that less water is evaporated in the basin, thus increasing the upwelled flow in the perimeter of the Salar or increasing the size of the lagoon and the elevation of the ground water depth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Instantaneous evaporation in the basin is proportional to the potential evaporation, and it can be as large as 90% of the precipitated water [ Vega , ], whereas the total evaporated water from the Salar can also be written as proportional to the potential evaporation [ Hornberger et al , ]. The proportional constant for computing total evaporation from the Salar is given, among others, by the size of the shallow wetland and its salinity [ de la Fuente and Niño , ], the ground water depth, and the soil salinity and humidity [ Nachshon et al ., ; Aminzadeh et al ., ; Hernández‐López et al ., ]. In this manner, the reduction in the potential evaporation may imply that less water is evaporated in the basin, thus increasing the upwelled flow in the perimeter of the Salar or increasing the size of the lagoon and the elevation of the ground water depth.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis is focused on Salar del Huasco (Figure ), located 3800 m above sea level (20.274°S, 68.883°W), where several research studies have been conducted [ Herrera et al ., ; Dorador et al ., ; de la Fuente , ; Hernández‐López et al ., ]. For the purposes of this article, a combination of field observations, satellite products and atmospheric reanalysis are used to calibrate the downscaling and the parameters of the model, and also to evaluate the performance of the spectral model (Figure ).…”
Section: Methodsmentioning
confidence: 99%
“…The hydrological functioning of the high Andean basins in the Altiplano region is characterized by semi-arid to hyper-arid climate and endorheic conditions [1]. In this area, water is crucial for natural habitats, industry, and agriculture.…”
Section: Introductionmentioning
confidence: 99%
“…Shokri and Or (2011) showed that the vertical diffusion of water vapor across ξ is the transport mechanism that mobilizes water vapor toward the atmosphere. Sophisticated models that consider vertical transport of water (liquid and gas phases) from the water table to the surface can be implemented for computing E (Hernández‐López et al, 2014, 2016; Sakai et al, 2009). However, these models require solving the water transport equations in the soil and coupling them to the atmospheric boundary layer (Davarzani et al, 2014), which makes them difficult to use in hydrological systems where surface water and ground water interact.…”
Section: Introductionmentioning
confidence: 99%